Aged Microglia in Neurodegenerative Diseases: Microglia Lifespan and Culture Methods - Yoo, Hyun-Jung; Kwon, Min-Soo (Frontiers in Aging Neuroscience, 2022)
Microglia have been recognized as macrophages of the central nervous system (CNS) that are regarded as a culprit of neuroinflammation in neurodegenerative diseases. Thus, microglia have been regarded as a cell that should be suppressed for maintaining homeostatic CNS environment. However, microglia ontogeny, fate, heterogeneity, and their function in health and disease have been defined better with advances in single cell and imaging technologies, and how to maintain homeostatic microglial function has become an emerging issue for targeting neurodegenerative diseases. Microglia are yolk-sac origin of long-lived cells and have limited repopulating capacity. So, microglial perturbation in their lifespan is associated with not only neurodevelopmental disorders, but also neurodegenerative diseases with aging. Considering that microglia are long-lived cells and may lose their functional capacity as they age, we can expect that aged microglia contribute to various neurodegenerative diseases. Thus, understanding microglial development and aging may represent an opportunity for clarifying CNS disease mechanism and developing novel therapies.